1998
DOI: 10.1007/s004190050177
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelectroelastic Green's function and its application for bimaterial of piezoelectric materials

Abstract: For a two-dimensional piezoelectric plate, the thermoelectroelastic Green's functions for bimaterials subjected to a temperature discontinuity are presented by way of Stroh formalism. The study shows that the thermoelectroelastic Green's functions for bimaterials are composed of a particular solution and a corrective solution. All the solutions have their singularities, located at the point applied by the dislocation, as well as some image singularities, located at both the lower and the upper half-plane. Usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(19 citation statements)
references
References 16 publications
0
19
0
Order By: Relevance
“…Thus, A ( = 1, 2, 3, 4) can be determined by (22), (25), and (33). A 4 ( = 1, 2, 3, 4) and A 5 can be determined by (37a), (37b), (38a), and (38b).…”
Section: Green's Functions For a Line Heat Sourcementioning
confidence: 99%
See 2 more Smart Citations
“…Thus, A ( = 1, 2, 3, 4) can be determined by (22), (25), and (33). A 4 ( = 1, 2, 3, 4) and A 5 can be determined by (37a), (37b), (38a), and (38b).…”
Section: Green's Functions For a Line Heat Sourcementioning
confidence: 99%
“…When the thermal effects are considered, Qin and Mai [33] derived a series of two-dimensional Green's functions for the anisotropic pyroelectric material with cracks, holes, and inclusions. Chen [34] derived a compact three-dimensional general solution for transversely isotropic pyroelectric materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These materials have been widely applied in the industry for fabricating devices including sensors, transducers, and actuators in some of the most promising areas such as aerospace industry and biotech. To enhance understanding of electromechanical coupling mechanism in piezoelectric materials and to explore their potential applications in practical engineering, numerous investigations, either analytically or numerically, have been reported over the past decades [3][4][5][6][7][8][9][10][11]. Due to the limitation of analytical methods which are available for problems with simple geometries and loading conditions numerical methods are usually employed in solving most practical problems [5,12].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore the mechanical response of structures excited by thermal loading is of increasing interest in engineering research and a large number of investigations have been made on these subjects. For example, theoretical analysis of the control of displacement was developed for a composite rectangular plate constructed from an isotropic elastic layer and a piezoelectric layer due to nonuniform heat supply [7], and the thermal stress distribution in a particle-reinforced functionally gradient material (FGM) [8] or piezo-thermoelastic plate [9,10] was obtained. On the other hand, the investigation of the effects of temperature on piezoelectric sensors found that even moderate fluctuations of temperature within 200 • C could significantly change the voltage reading from the sensors [11].…”
Section: Introductionmentioning
confidence: 99%